Implementation of Sharia Principles in the Promotion and Distribution of Mie Jahat Patemon Bangkalan MSME Products - Khoirotun Nisa (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the application of sharia principles in promotion and distribution at the